2004
DOI: 10.1017/s0950268803001262
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of severe invasive group-G streptococcal infections and molecular typing of the isolates in Japan

Abstract: The number of patients with severe invasive group-G streptococcal (Streptococcus dysgalactiae subsp. equisimilis) infections has been increasing in Japan. The emm genotypes and SmaI-digested pulsed-field gel electrophoresis DNA profiles were variable among the strains isolated, suggesting there has not been clonal expansion of a specific subpopulation of strains. However, all strains carried scpA, ska, slo and sag genes, some of which may be involved in the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 6 publications
2
72
1
Order By: Relevance
“…equisimilis possesses many virulence factors shared with GAS, such as M protein (Fischetti, 1989;Schnitzler et al, 1995), streptolysin O (Gerlach et al, 1993;Okumura et al, 1994), streptolysin S (Humar et al, 2002) and streptokinase (Walter et al, 1989;Ikebe et al, 2004). It has been suggested that these factors were transmitted from GAS to this species (Kalia et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…equisimilis possesses many virulence factors shared with GAS, such as M protein (Fischetti, 1989;Schnitzler et al, 1995), streptolysin O (Gerlach et al, 1993;Okumura et al, 1994), streptolysin S (Humar et al, 2002) and streptokinase (Walter et al, 1989;Ikebe et al, 2004). It has been suggested that these factors were transmitted from GAS to this species (Kalia et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…equisimilis strains having group A antigen rather than group C or G antigen have also been reported (Bert & Lambert-Zechovsky, 1997;Brandt et al, 1999;Katsukawa et al, 2002 Notably, S. dysgalactiae subsp. equisimilis possesses many virulence factors shared with GAS, such as M protein (Fischetti, 1989; Schnitzler et al, 1995), streptolysin O (Gerlach et al, 1993Okumura et al, 1994), streptolysin S (Humar et al, 2002 and streptokinase (Walter et al, 1989;Ikebe et al, 2004). It has been suggested that these factors were transmitted from GAS to this species (Kalia et al, 2001).…”
mentioning
confidence: 99%
“…dysgalactiae subsp. equisimilis (SDSE) is a β-hemolytic streptococci that is increasingly prevalent in human infections, having the similar clinical spectrum of diseases caused by S. pyogenes (Group A Streptococcal infections, GAS) [1,2]. It presents as a pathogen in skin and soft-tissue infections, endocarditis, bacteremia, ocular infection, pneumonia, osteomyelitis, and meningitis [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Both species have antiphagocytic M protein, encoded by emm [10,35,36] and hyaluronic capsule [10,35]. There are, however, marked differences between them: SDSE, for example, lacks the whole set of genes encoding superantigens, which are mostly of phage origin (spe A, spe B, spe C, spe H, spe I, spe J, spe K, spe L, spe M, ssa, smez) [12,15,24,35,[38][39][40][41][42]. However, scarce occurrences of SDSE strains have been described, having one of those genes [32,43].…”
Section: Introductionmentioning
confidence: 99%
“…However, scarce occurrences of SDSE strains have been described, having one of those genes [32,43]. The only superantigen gene which is often found in SDSE strains is spe G, which encodes exotoxin G [12,22,24,32,35,36,[39][40][41][42]44]. Between both of these closely related bacteria, interspecies DNA transfer occurs [6,45,46] by means of mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%